Implementasi Konsep Michi-no-eki pada Strategi Desain Anjungan Jalan sebagai Pendukung Business Branding - Kartika Tiffania Fairuza Firdaus; Agung Kumoro Wahyuwibowo (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2024)
The concept of michi-no-eki has become a pilot study in several countries, such as Kenya and China, due to having been proven to be able to overcome the issue of inequality in areas crossed by roads. This research intends to analyze the implementation of the michi-no-eki concept on a road platform model in Kulon Progo Regency as a support for business branding. The method used is a comparative case study in Michi-no-eki in Japan to determine the basic considerations that can be implemented in the road platform design strategy in Kulon Progo Regency. The research results explain the recommendations for road platform models in Kulon Progo as supporting business branding, namely 1) located on National Road 3; 2) Has a rest function for road users with additional worship facilities; providing tourism information for road users and health facilities for local communities, and training facilities as well as direct selling depots for superior local products; 3) Accommodate the development of the community of artists, farmers and MSMEs; 4) Promote local agricultural products and processed products; and 5) implementing building architectural prototypes according to Kulon Progo Regent Regulation No. 87 of 2018 concerning Building Architectural Prototypes with Typical Kulon Progo Characteristics.